Dematerialization and heritage enhancement: actors, tools and challenges. - (:unkn) unknown (My University, 2025)
The dematerialization of documentary heritage through digitization presents transformative opportunities for preservation, accessibility, and engagement with Africa's rich archival resources. This presentation explores the multifaceted process of digitizing archives, highlighting the critical roles played by diverse stakeholders, including local communities, government agencies, non-governmental and international organizations, and heritage professionals. It examines the technological tools, such as high-resolution scanning, optical character recognition (OCR), artificial intelligence (AI), and cloud-based storage, that underpin effective digital archiving. The paper also addresses the benefits of digitization in preserving fragile documents, promoting efficient governance, and enabling wider access to African heritage. However, these opportunities are accompanied by unique challenges, such as inadequate funding, policy gaps, and limited digital literacy. To ensure the success and sustainability of digitization initiatives, the presentation offers strategic recommendations focused on strengthening policy frameworks, increasing investment, enhancing capacity building, and fostering international collaboration. Ultimately, the paper advocates for a collective and inclusive approach to digital transformation that safeguards Africa’s documentary heritage for future generations.
Keywords: African Research